Cloud Storage, Issues and Solution (International Journal of Engineering and Computer Science, 2014)
Cloud storage is one of the many services offered by the cloud computing. Cloud storage is much sought due to anytime, anywhere access using wide varieties of devices, for instance, laptop, desktop and smart phones. Due to these capabilities, a number of individuals as well as organizations are subscribing for this service from the various vendors existing in this area. These cloud providers differ from their services in a great deal. This work compares the offering of different storage provider considering the storage space, synchronization capabilities, pricing, compliances etc. Finally, we discussed the major issues that exist in cloud and methods to address them without compromising the cloud performance.